Pengaruh Good Corporate Governance dan Kinerja Keuangan Terhadap Potensi Terjadinya Fraudulent Financial Statement pada Perusahaan Pertambangan yang Terdaftar di BEI Tahun 2019-2022 - Julia Anisa; Sumiyati Sumiyati; Julia Julia (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
Along with the growth of competitors, companies want to display the best conditions through financial reports, but this can encourage management to commit financial statement fraud. This study aims to analyze the effect of managerial ownership, institutional ownership, independent commissioners, and leverage on the potential for fraudulent financial statements in mining companies listed on the IDX in 2019-2022. This type of research is quantitative research with the source, namely secondary data. The sample in this study was 84 company data calculated using purposive sampling technique. The results of this study indicate that managerial ownership and institutional ownership have no effect on fraudulent financial statements in mining companies in 2019-2022. Meanwhile, independent commissioners and leverage influence fraudulent financial statements in mining companies in 2019-2022.